Al-Alaqatu Al-Ilmiyati Baina Al-Ulamai Al-Jawina Wa Al-Faulati Al-Usminiyyina Fi Al-Qarni Al-Sadisa Asyara Al-Miladi Ila Qarni Al-Tamina Asyara Al-Miladi - Nuha, Ulin (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2022)
Abstract For approximately five centuries, starting from 1571 and actually ending in 1924, the Ottoman Empire controlled the scientific centers in the Hejaz City. During that time, Ulama Jawi enjoyed the golden age of science. Thoriq Aziz, in his book entitled "Ulama-Ulama Nusantara yang Mempengaruhi Dunia" documented at least three Ulama from Indonesia who had been Imam al-haramain during that period. They are Sheikh Junaid al-Batawi, Sheikh Nawawi al-Jawi al-Bantani, and Sheikh Ahmad Khatib al-Minangkabawi. At that time, Ulama Jawi, most of whom came from Indonesia, had a big role in enlivening scientific activities at Haramain. One of Ulama Jawi who became great scholars in Haramain, usually had students in Haramain who later also became great scholars in Haramain. Among them was come from Sambas, Shaykh Ahmad bin Abdu Somad Sambas. Many of his students became great scholars such as Sheikh Tholhah Gunung Jati Cirebon, Sheikh Ahmad Kholil Bangkalan Madura, Sheikh Abdul Qodir Al Bantani, who sent down students, namely Sheikh Abdul Aziz Cibeber and Sheikh Asnawi Banten. Other Ulama Jawi who are very well known as great scholars at Haramain are Shaykh Nawawi al Bantani, Sayid Ahmad an Nahrowi Al Banyumasi, Sheikh Mahfudz Al Turmizi, Sayidi Sheikh Ubaidillah Surabaya, Sayidi Sheikh Muhammad Ilyas Sokaraja, Sayidi Sheikh Abdullah Tegal, Sayidi Sheikh Abdullah Wahab Rohan Medan, Sayid Sheikh Abdullah Batangpau, Sayyidi Sheikh Muhmmad Ilyas Sokaraja, Sayyidi Sheikh Abdul Aziz bin Abdu Somad al Bimawi, and Sayidi Sheikh Abdullah and Sayidi Sheikh Abdul Manan, Sayidi Sheikh Ahmad Abdul Hadi Giri Kusumo Mranggen Demak, Sheikh Baqir Zaenal Abidin jogja and Shaykh Idris Jamsaren. In that golden age of sciences period of approximately five centuries, a very beautiful relationship was established between Ulama Jawi who played the role of Imam al-haramain as well as enriched scientific activities in Haramain and the Ottoman Empire who acted as protectors and providers of facilities for all religious and scientific activities in Haramain. Keywords: Scientific Network, Ulama Jawi and Ottoman Empire